Uma versão generalizada do Teorema de Extrapolação para operadores não-lineares absolutamente somantes - Santos, Lisiane Rezende dos (2016)
In this work we study a recent general version of the Extrapolation Theorem, due to Botelho, Pellegrino, Santos and Seoane-Sep ulveda [6] that improves and uni es a number of known Extrapolation-type theorems for classes of mappings that generalize the ideal of absolutely p-summing linear operators.